Alarming Prevalence of Sulfaquinoxaline Residue in Poultry Meat Sold in Jammu Region of UT of J&K - Lenesha Manhas; Nrip Kishore Pankaj; Pawan Kumar Verma; Shafiq-ur-Rahman; Ajay Kumar Gupta (The Indian Veterinary Journal, 2024)
The study was planned to screen Sulfaquinoxaline (SQX) residue status in chicken tissue in Jammu, J&K. Tissue samples from various districts of Jammu, gathered and analyzed for SQX residues using RP-HPLC-UV. Mobile phase was 0.01M ammonium acetate and acetonitrile (43:57), at 1ml/min flowrate, r2=0.999, Rt: 3.813 minutes, with recovery ³ 77.484% in chicken tissues. The residue level of SQX, found over 70, 10 and 25% beyond the established MRL respectively in liver, kidney and muscles from district Jammu. Liver samples up to 50, 25, 45 and 100% from Samba, Reasi, Kathua and Udhampur respectively, had residue over the established MRL.